Implementation Of Adminsitrative Management at SMA Negeri 2 Samarinda - Ananiah, Ananiah; Hamdani, Hamdani; Setiawan, Agus (el Buhuth: Borneo Journal of Islamic Studies, 2020)
As one of the schools that is in great demand by students, SMA Negeri 2 Samarinda is an educational institution that has a good and systematic quality of educational services. So from this, it can encourage an effective and efficient educational process. This is undoubtedly influenced by the implementation of administrative management, which is reflected in the implementation of the duties of administrative staff and library staff in providing good administrative services and management to students at school. The purpose of this study was to determine the implementation of administrative management at SMA Negeri 2 Samarinda through the implementation of the duties of administrative staff and library staff. This research was conducted at SMA Negeri 2 Samarinda. This study uses a qualitative approach, namely an approach based on phenomena or realities that occur in the field. Sources of data in this study were the Principal, administrative staff, and library staff, using data collection techniques in the form of interviews, observation, and documentation. Data analysis techniques in research, namely using data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that SMA Negeri 2 Samarinda carries out the implementation of school administration management well. This is illustrated by the implementation of administrative staff duties, which include staff and student management, presentation of school data, preparation of an inventory of archival storage equipment, and implementation of school environment maintenance. And also, the duties of a librarian include procurement, processing, and empowerment of library books. So that from the implementation of administrative management, can encourage good educational services in achieving the desired educational goals. Keywords: Implementation, Management, Service